Evaluation of adhesin genes and risk factors associated with urinary tract infections by drug-resistant uropathogenic Escherichia coli in North of Iran - Raheleh Sheikhi; Mohammad Esmaeil Amini; Leila Alidoust; Zahra Atrkar Roushan; Iraj Nikokar (Journal of Infection in Developing Countries)
Background: Uropathogenic Escherichia coli (UPEC) isolates, have a wide variety of virulence factors to promote colonization and survival in the urinary tract. This study aimed to evaluate adhesin genes, biofilm formation ability, antibiotic resistance profiles of UPEC strains, and the related risk factors in patients with UTIs caused by drug-resistant UPEC.